Impact of COVID-19 Pandemic on Pediatrics and Pediatric Transplantation Programs - Lobritto, Steven; Danziger-Isakov, Lara; Michaels, Marian G.; Mazariegos, George V. (Frontiers in Pediatrics, 2020)
COVID-19 has dramatically altered the health care landscape and disrupted global health and world economics in ways that are still to be measured. Its impact on children with chronic conditions or those undergoing transplantation is evolving. The organ specific manifestations in children will be reviewed and treatment strategies outlined. The impact on pediatric transplantation in the United States over the initial six months of the pandemic has shown significant regional variation and lags persist in resumption of normal transplant activity, particularly for living related transplantation. Finally, guidelines regarding return to school will be discussed.